Reflective Thinking and Islamic Jurisprudence Traditions (Fatwa) - Ahmad Asrin; Hasan Bakti Nasution (Budapest International Research and Critics University, 2022)
The aims of this study are to find out the Reflective Thinking and Islamic Jurisprudence Traditions (Fatwa). This study use qualitative research method. From the description that the author describes, several conclusions can be drawn:1.Reflective thinking is someone who must be active and careful in understanding the problem, linking the problem with the knowledge that has been obtained and considering carefully in solving the problem.2.The characteristics of reflective thinking include:3.The tradition of Islamic Jurisprudence is a habit of legal experts in obtaining a set of guidelines, rules, and regulations from decisions that are regulated based on the Qur'an, sunnah, analogy, consensus, and research disciplines.4.Usul fatwa is the basis or argument used by a mufti in answering questions related to sharia law, both for individual and collective interests in the context of the interests of the community which are not binding.5.In addition to being a mufti who is qualified in his field, he must also be able to use the potential of relative thinking so that the fatwa produced is protected from all forms of misguidance and provides benefits for the benefit of the community.